Re-totalizing Culture: Breathing the Intangible into Museum Practice? - Shelton, Anthony (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2014)
With the growth of concern over diminishing cultural diversity, homogenization, and the preservation of tangible patrimony, UNESCO has increasingly assumed a lead position in devising new legislative instruments – programs, proclamations, conventions, and treaties – for the safeguard and regulation of cultural heritage. This cultural policy has been re-directed in the last two decades by a newly emergent and confident cosmopolitan political bloc that has attempted to reverse the organization’s Occidental bias by extending the protection it gives to tangible heritage to include intangible cultural expressions. This new political interest coincides with wider demands for the re-totalization of both aspects of culture aimed at encouraging the institutional use of vernacular interpretations in place of typological and externally imposed classifications. While these movements share a common interest in the decolonization of institutional culture, there is no overarching consensus on the means by which authority over interpretation can be returned to and exercised by originating communities and practitioners. To support its relatively new cultural mandate, UNESCO has revised its definitions of culture. These re-articulations – largely appropriated from specific anthropological discourses – expand the concept of culture to include its tangible and intangible manifestations, and provide a legitimating moral and intellectual authority to promote its wider acceptability. This essay represents a modest attempt to define and trace the influence of part of the rhetoric generated by globalized institutional cultures on museum practice and to raise questions on the current choices museums have been called to make.